Facebook, the Conservatives and the Risk to Fair and Open Elections in the UK. Issue 3 (26th August 2016) - Moore, Martin
Abstract: The Conservative party spent £1.2 million on Facebook during the UK 2015 general election campaign. This enabled the party to target specific voters in marginal constituencies with tailored messages. Their use of Facebook in 2015 shows how central digital media had become to their campaign communication. It also shows, however, that this communication may be compromising the principles of fair and open elections in the UK, for example by allowing parties to effectively bypass constituency spending limits and avoid transparency. Unless electoral legislation and regulation are changed to take account of developments in digital media they are liable to become increasingly anachronistic and ineffective.